Karaktristik Pola Aliran Pemisahan Kerosene-Water Pada Pipa T-Junction Sudut 90˚ Dan Radius 25 mm Dengan Bahan Pleksiglass - Kms. Ridhuan (JURNAL MECHANICAL, 2012)
Abstract Tests with the fluid flow pattern visualization kerosene (kerosene)-water through a pipe with a T-junction has been performed at the Laboratory of Fluid Mechanics, Faculty of Engineering, Gadjah Mada University. Tests performed on the test section of T-Junction with an angle of 90 ˚ and 25 mm bend radius. Fleksiglass material with a diameter of 1.5 inches with kerosene (kerosene) and water as working fluid. To determine the flow pattern is done by kerosene and set the superficial velocity of water. Kerosene superficial velocity (Jk) and superficial velocity of water (Jw) that flowed in the test section is set by using a valve and measured using flow meters at a range of values Jk = 0.10 m / s - 0.22 m / s and Jw = 0 , 10 m / s - 0.40 m / s. Flow patterns that occur during the research process was recorded by using cameras and observed visually with the movement slowed. As a result, it is known that the flow pattern occurring in this study is stratified (S), Stratified Wavy (SW), Three Layer (3L), Stratified Wavy Water in Oil (SWw / o), and dispersed (D). For kerosene-water separation of the most well occur in Stratified Wavy flow pattern at a speed suprfisial kerosene (Jk) 0.14 to 0.18 m / s and superficial velocity of water (Jw) 0.15 to 0.25 m / s. In the superficial mixture velocity (Jmix) 0.34 to 0.43 m / s. And for kerosene-water separation of the less well occur in dispersed flow pattern (D) velocity suprficial kerosene (Jk) 0.12 m / s down and 0.20 m / s upward. Superficial velocity of water (Jw) 0.15 m / s down and 30 m / s upward. In the superficial mixture velocity (Jmix) below 0.56 m / s. And on top of 0.60 m / s.Keywords: flow patterns, kerosene-Water, T-junction.